We’ll Just Edit that Right Out of Here: A Chat with Roo Borson - Quinn, Mike; Wilson, Tim (Studies in Canadian Literature, 1992)
Roo Borson talks about the importance of memory to her work. In Whole Night Coming Home (1984), "memory turns the past into fiction . . . writing about it takes it one step further." Her work becomes, in Quinn’s words, "word paintings of memories." She claims that she is "North American" in that she has an affinity with the landscape of North America. Her poetry is very "flesh and blood"; she shares with Daphne Marlatt and Erin Mouré a "sensuousness in the world that is made manifest in the writing." Although she claims that she doesn’t write for a particular audience, "The motive for writing poetry is somehow to sing or to speak. To sing or speak requires a listener." What matters to her is not her critical reception but that the individual reader finds something meaningful in her work.